The Effect of Work Discipline, Work Environment and Work Motivation on Employee Performance - Maulidiah, Uzla; Baskoro, Heru (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This research aimed to investigate the effects of Work Discipline, Work Environment, and Work Motivation on Employee Performance at PT Hillwood. A quantitative approach was adopted, with a sample size of 65 respondents. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS). The findings indicated that while Work Discipline has a significant influence on employee performance, it exhibits a negative relationship. In contrast, both Work Environment and Work Motivation were found to have a positive and statistically significant impact on employee performance at PT Hillwood.